Demand for quality-differentiated beef in Japan - Sayed H. Saghaian; Michael R. Reed (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
In this article, we apply a model of vertical product differentiation to the Japanese beef market. We theoretically derive a system of consumer demand functions for quality-differentiated beef in Japan. We choose a particular utility function which is nonlinear in the consumption of the quality-differentiated product and linear in the consumption of all other goods. We employ a seemingly unrelated econometric model to estimate Japanese consumer demand functions for four beef types from the four origins. The empirical results show Japanese consumers prefer domestically produced beef to imported US and Australian. We also find seventeen substitution and two complementary effects among the various origins.
Keywords: 330; Rindfleisch; Produktdifferenzierung; Produktqualität; Konsumentenverhalten; Japan